2014
DOI: 10.1371/journal.pone.0104842
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis between Central Corneal Thickness and Intraocular Pressure in Juveniles in Northern China: The Jinan City Eye Study

Abstract: PurposeTo determine the distributions and relation of central corneal thickness (CCT) and intraocular pressure (IOP) by NT-530P in Chinese juveniles, and the effect of gender, age, height, weight and refractive errors on the CTT and IOP.MethodsCCT and IOP of 982 eyes in 514 juveniles aged from 7 to 18 years were measured with NT-530P. Multi-linear regression and ANOVA analysis were used to analyze the relation of CCT and IOP, and the effect of gender, age, height, weight, refractive condition on CCT and IOP re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 39 publications
3
29
2
3
Order By: Relevance
“…Therefore, a thinner cornea may lead to underestimation and a thicker cornea overestimation of the true IOP. [16][17][18] In this present study, we found that diabetes and poorer glycemic control have predominately direct associations with higher IOP and only minimal indirect associations through thicker CCT. These findings reassure that high IOP among diabetes is not an overestimate due to thicker CCT.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Therefore, a thinner cornea may lead to underestimation and a thicker cornea overestimation of the true IOP. [16][17][18] In this present study, we found that diabetes and poorer glycemic control have predominately direct associations with higher IOP and only minimal indirect associations through thicker CCT. These findings reassure that high IOP among diabetes is not an overestimate due to thicker CCT.…”
Section: Discussionmentioning
confidence: 68%
“…14,15 Greater CCT may lead to an ''overestimation'' of the true IOP. [16][17][18] It remains unclear whether the diabetes-IOP association is mediated via thicker CCT among persons with diabetes. We hypothesize that thicker CCT in persons with diabetes partially explains the association between diabetes and IOP.…”
mentioning
confidence: 99%
“…Thin corneas may lead to an underestimation of IOP, 35,36 but increased IOP in these nontreated Ctns À/À mice may have been caused by corneal sclerosis or scarring. 37 In contrast, physiological IOPs were observed in the HPSC-engrafted Ctns À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown specular microscopy measurements of CCT are considerably lower than ultrasound pachymetry measurements of CCT [7, 14]. In our study, corresponding to parents’ consent only a single contact measurement was taken, and therefore, the authors decided to measure IOP with gold standard Goldmann applanation tonometer and CCT measurement was documented with noncontact specular microscope.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies found a relationship between ethnicity and IOP. In addition, IOP and CCT values have proven to be different among children from various races including black and white [5, 6], Chinese [7, 8], Turkish [9], Japanese [10], Indian [11] and Malay pediatric population [12]. …”
Section: Introductionmentioning
confidence: 99%